Patients With Chronic Low Back Pain Have an Individual Movement Signature: A Comparison of Angular Amplitude, Angular Velocity and Muscle Activity Across Multiple Functional Tasks - Christe, Guillaume; Aussems, Camille; Jolles, Brigitte M.; Favre, Julien (Frontiers in Bioengineering and Biotechnology, 2021)
Despite a large body of evidence demonstrating spinal movement alterations in individuals with chronic low back pain (CLBP), there is still a lack of understanding of the role of spinal movement behavior on LBP symptoms development or recovery. One reason for this may be that spinal movement has been studied during various functional tasks without knowing if the tasks are interchangeable, limiting data consolidation steps. The first objective of this cross-sectional study was to analyze the influence of the functional tasks on the information carried by spinal movement measures. To this end, we first analyzed the relationships in spinal movement between various functional tasks in patients with CLBP using Pearson correlations. Second, we compared the performance of spinal movement measures to differentiate patients with CLBP from asymptomatic controls among tasks. The second objective of the study was to develop task-independent measures of spinal movement and determine the construct validity of the approach. Five functional tasks primarily involving sagittal-plane movement were recorded for 52 patients with CLBP and 20 asymptomatic controls. Twelve measures were used to describe the sagittal-plane angular amplitude and velocity at the lower and upper lumbar spine as well as the activity of the erector spinae. Correlations between tasks were statistically significant in 91 out of 99 cases (0.31 ≤ r ≤ 0.96, all p < 0.05). The area under the curve (AUC) to differentiate groups did not differ substantially between tasks in most of the comparisons (82% had a difference in AUC of ≤0.1). The task-independent measures of spinal movement demonstrated equivalent or higher performance to differentiate groups than functional tasks alone. In conclusion, these findings support the existence of an individual spinal movement signature in patients with CLBP, and a limited influence of the tasks on the information carried by the movement measures, at least for the twelve common sagittal-plane measures analysed in this study. Therefore, this work brought critical insight for the interpretation of data in literature reporting differing tasks and for the design of future studies. The results also supported the construct validity of task-independent measures of spinal movement and encouraged its consideration in the future.